Galectins in Chagas Disease: A Missing Link Between Trypanosoma cruzi Infection, Inflammation, and Tissue Damage - Poncini, Carolina V.; Benatar, Alejandro F.; Gomez, Karina A.; Rabinovich, Gabriel A. (Frontiers in Microbiology, 2022)
Trypanosoma cruzi, the protozoan parasite causative agent of Chagas disease, affects about 7 million people worldwide, representing a major global public health concern with relevant socioeconomic consequences, particularly in developing countries. In this review, we discuss the multiple roles of galectins a family of β-galactoside-binding proteins, in modulating both T. cruzi infection and immunoregulation. Specifically, we focus on galectin-driven circuits that link parasite invasion and inflammation and reprogram innate and adaptive immune responses. Understanding the dynamics of galectins and their β-galatoside-specific ligands, during the pathogenesis of T. cruzi infection and elucidating their roles in immunoregulation, inflammation and tissue damage, offer new rational opportunities for treating this devastating neglected disease.